Open surgery of complex long segment (giant) glomus spinal arteriovenous malformation - Deo, Alok; Aryal, Sameer; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2020)
Spinal arteriovenous malformation occurring in the pediatric population (under 15 years) initially complain of pain as the first symptom which is often over looked. In almost all, diagnosis is delayed resulting in weakness. Angiogram provides correct diagnosis in all cases. Radical microsurgical excision tends to offer best long-term result. Here we present a 7-year-old girl referred to us for lumbar puncture with provisional suspicion of meningitis. She had history of fever for two days and signs of meningism were present. On examination, she was stable and had complains of headache. Her previous history suggested she had continuous backache since childhood and had visited multiple centers previously for the problem. A detailed work up revealed a long segment spinal space occupying lesion. CT angiogram showed spinal arteriovenous malformation. Laminoplasty and open microsurgical excision of arteriovenous malformation was performed. Her hospital stay was uneventful and was discharged in stable condition. Early recognition, accurate diagnosis and prompt surgical treatment may result in significant improvement of neurological function.